Analysis of Bioactive Compounds in Functional Groups of Morinda Citrifolia Leaf Extract and Pearl Grass Using FTIR (Fourier Transform Infrared) Spectrophotometer as Antioxidants against Kidney Cell Damage Caused by Kidney Failure - Nurmansyah, Anggik Eka; Puspita, Safira Cahya; Hidayati, Irul; Agustina, Eva; Lusiana, Nova; Purnamasari, Risa; Andiarna, Funsu (International Conference on Sustainable Health Promotion, 2025)
Kidney failure is a non-communicable disease that can be life-threatening. One plant that is often used as herbal medicine is noni leaf and pearl grass because they contain bioactive compounds. The purpose of this study was to analyze the differences in functional groups found in noni leaf and pearl grass extracts as antioxidants against kidney cell damage caused by kidney failure. Leaf extraction was performed using the maceration method with 70% ethanol as the solvent. Phytochemical testing was conducted qualitatively and also involved a literature review to determine the effects of bioactive compounds. The results of the pearl grass extract test showed strong peaks at wavelengths of approximately 3291 cm⁻¹ (O–H group), 1637 cm⁻¹ (aromatic C=C group), and 1034 cm⁻¹ (C–O alcohol group), indicating the presence of phenolic and flavonoid compounds. The FTIR spectrum results on noni leaves showed peaks at 3278 cm⁻¹ (O–H/N–H), 1630 cm⁻¹ (C=O/aromatic C=C), and 1052 cm⁻¹ (C–O), indicating the presence of carboxylic acid compounds, amines, and phenolic components. The functional groups of these compounds have significant potential to repair kidney cell damage caused by kidney failure. Based on the FTIR analysis results and supporting literature, it can be concluded that noni leaves are more effective than pearl grass in reducing kidney cell damage caused by kidney failure.